2018
DOI: 10.1136/bmjopen-2018-022621
|View full text |Cite
|
Sign up to set email alerts
|

Work-related mobility and experiences of gender-based violence among female sex workers in Iringa, Tanzania: a cross-sectional analysis of baseline data from Project Shikamana

Abstract: ObjectivesTo examine how work-related mobility among female sex workers (FSWs) is associated with gender-based violence (GBV) in Iringa, Tanzania.DesignCross-sectional analyses were conducted on baseline data gathered between October 2015 and April 2016 from FSWs participating in Project Shikamana, a community empowerment-based combination HIV prevention intervention.SettingParticipants were recruited for the baseline study using venue-based time-location sampling in two communities in Iringa, Tanzania.Partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 40 publications
4
24
2
Order By: Relevance
“…Moreover, to the best of our knowledge, this is the first study on the relationship between client-perpetrated GBV and sex work-related mobility in post-conflict settings. However, our finding is consistent with previous studies reporting that mobile FSWs were at increased odds of client-perpetrated GBV (9,10,30). This is because mobile FSWs tend to have less control over their work environment and many of the male clients of FSWs tend to refuse to use condoms with the new coming mobile FSWs (30).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Moreover, to the best of our knowledge, this is the first study on the relationship between client-perpetrated GBV and sex work-related mobility in post-conflict settings. However, our finding is consistent with previous studies reporting that mobile FSWs were at increased odds of client-perpetrated GBV (9,10,30). This is because mobile FSWs tend to have less control over their work environment and many of the male clients of FSWs tend to refuse to use condoms with the new coming mobile FSWs (30).…”
Section: Discussionsupporting
confidence: 93%
“…Only a few studies examined the relationship between client-perpetrated GBV and FSWs’ monthly income. In Tanzania, the income level did not significantly affect the occurrence of client-perpetrated GBV (10). However, in Northern Ethiopia low earning FSWs were more likely to suffer from client-perpetrated GBV (34).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A multi-country study revealed the odds of experiencing IPV was 33% higher amongst women who were employed in comparison to those who were unemployed [ 58 ]. Researchers found that health care workers were more likely to experience GBV [ 57 , 58 , 61 ], particularly emotional violence. Nurses and midwives [OR: 4.06; 95% CI (1.20, 13.74)] were more likely to experience workplace violence in comparison to other health care workers [ 28 , 30 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Baseline data are available. 64,69 Results presented at conferences suggest that intervention participants were significantly less likely to become infected with HIV at follow-up, had lower HIV incidence, reported more consistent condom use, and experienced less gender-based violence compared to participants in the control group. 70,71 Final results are forthcoming.…”
Section: -90-90 Implementation Studiesmentioning
confidence: 99%